Media Capture by Banks - Ruben Durante; Andrea Fabiani; Luc Laeven; José-Luis Peydró (Institute of Labor Economics (IZA), 2022)
Do media slant news in favor of the banks they borrow from? We study how lending connections affect news coverage of banks earnings reports and of the Eurozone sovereign debt crisis on major newspapers from several European countries. We find that newspapers cover announcements by their lenders - relative to those of other banks - significantly more when they report profits than when they report losses. Such pro-lender bias is stronger for more leveraged outlets and banks, and operates on the extensive margin for general-interest newspapers and on the intensive margin for financial newspapers. Regarding the Eurozone crisis we find that newspapers connected to banks more exposed to stressed sovereign bonds are more likely to promote a narrative of the crisis favorable to banks and to oppose debt-restructuring measures detrimental to creditors. Our findings support the concern that financial distress and increased dependence on creditors may undermine media companies' editorial independence.
Keywords: G21; L82; 330; media bias; banks; newspapers; earnings reports; Eurozone crisis